Sejarah Pergerakan Perempuan Indonesia Abad 19 – 20: Tinjauan Historis Peran Perempuan dalam Pendidikan Bangsa - Silvy Mei Pradita (Universitas Muhammadiyah Prof. Dr. Hamka, 2020)
The discourse on the role of women never ends up talking. Women as actors in domestic work or their roles in the public sphere are not long debated, become discussions everywhere. One of them is about the women's movement. A movement created by women activists whose task is to promote the position of women. Step by step taken by women figures on the trajectory of history proves that Indonesian women have truly laid the foundation of women in the name of social justice. This research aims to make the understanding of history as the foundation for women who are active today in fighting for social and political rights. The research method used is the historical method. The result is that the movement of women from the end of the 19th century to the most recent one has been fluctuating or tidal. The strong waves raised by female figures in voicing women's rights in all fields were born from gender injustice. Therefore, Indonesian women leaders have given an example, women today have the responsibility to continue the struggle. Abstrak Diskursus mengenai peran perempuan tidak pernah habis dibicarakan. Perempuan sebagai aktor pekerjaan domestik ataupun perannya di ruang publik tidak usang diperdebatkan, dijadikan wacana diskusi di mana-mana. Salah satunya mengenai pergerakan perempuan. Gerakan yang diciptakan para aktivis perempuan secara mendasar bertujuan untuk mengangkat posisi perempuan. Langkah demi langkah yang dilakukan para tokoh perempuan pada lintasan sejarah membuktikan bahwa perempuan Indonesia bersungguh-sungguh meletakkan dasar pergerakan perempuan atas nama kemanusiaan dan keadilan sosial. Penelitian ini bertujuan untuk menjadikan pemahaman sejarah sebagai landasan pergerakan perempuan di masa sekarang dalam memperjuangkan hak-hak sosial dan politik. Metode penelitian yang digunakan adalah metode historis. Hasilnya adalah pergerakan perempuan sejak akhir abad 19 sampai yang paling mutakhir bersifat fluktuatif atau pasang surut. Gelombang kencang yang diembuskan para tokoh perempuan dalam menyuarakan hak perempuan dalam segala bidang lahir dari ketidakadilan gender. Maka dari itu, para tokoh perempuan Indonesia telah mencontohkan, perempuan hari ini punya tanggung jawab melanjutkan perjuangan.